Seismicity Analysis and Velocity Structure of Two-phase Geothermal Field in Southern Bandung - Al Hakim, Muhamad Firdaus (Jurnal Ilmiah MTG, 2023)
Over a duration of six months, we conducted a microearthquake analysis to characterize the subsurface conditions in the two-phase geothermal field located in Southern Bandung. Throughout the study, a total of 754 microearthquake (MEQ) data were recorded from at least 15 monitoring stations. After selection process of the dataset, 362 events were selected based on their azimuthal gap angle being less than 180°. Initially, the earthquake locations were determined using the Geiger method. Subsequently, we updated the hypocenter locations through simultaneous inversion, incorporating 1D velocity structure and 3D tomographic inversion. Our analysis revealed three primary seismicity clusters, which likely correspond to the injection and production activities within the geothermal field. The southern cluster aligns with the injection wells, extending from a depth of 1 km to 8 km, suggesting that the MEQ events were induced by injection activity. In the production area, a higher concentration of events is observed, densely distributed between depths of 1 km and 3 km. We suspect that the third cluster is associated with the development activity of a steam-dominated geothermal field located east of the main field. Notably, low Vp/Vs values near the surface are detected and exhibit increased thickness towards the north. These characteristics are interpreted as indicative of the steam zone, as the anomaly's location aligns closely with the production area. The thickening of the low Vp/Vs zone towards the north suggests the presence of steam as the impact of fluid extraction in the region, leading to a decline in pressure.